Antenatal steroids and fluid balance in very low birthweight infants. Issue 6 (5th May 2005) - Dimitriou, G; Kavvadia, V; Marcou, M; Greenough, A
Abstract : Objectives: To determine if insensible water loss (IWL) differed between infants exposed or not exposed antenatally to corticosteroids and to explore possible mechanisms for the early postnatal diuresis associated with antenatal steroid exposure. Design: Retrospective analysis of prospectively collected data. Setting: Level three neonatal intensive care unit. Patients: Ninety six infants, median gestational age 27.5 weeks (range 23–33). Main outcome measures: Comparison of the IWL, urine output and osmolality, fluid input, electrolyte imbalance, respiratory illness severity (as assessed by surfactant requirement, maximum peak inspiratory pressure, and inspired oxygen concentration), and cardiovascular status (as assessed by inotrope requirement) between infants with antenatal corticosteroid exposure and gestational age matched controls. Results: The infants exposed to antenatal steroids differed significantly from the controls in having both a lower IWL (p  =  0.0135) and a higher urine output (p  =  0.0036) on day 1, and fewer developed hyponatraemia (p  =  0.027) on day 2. Fewer of those exposed to antenatal steroids required inotropes (p  =  0.06), but their respiratory status was similar to that of the controls. Conclusions: Infants exposed to antenatal corticosteroids have a lower IWL. The results suggest that greater skin maturation, but also better perfusion rather than less severe respiratory status, explains the early diuresis in infants exposed to antenatal steroids.